Isolation and complete genome analysis of Porcine Parvovirus 1 from swine with reproductive failure in southern India - P. Mohanapriya; S. Parthiban; K. Reshma; M. Parthiban; M. Murugan; A. Ramesh; K. Senthilkumar; P. Raja; P. Jalantha; Jagadish Hiremath; S. S. Patil; M. Kalyana Chakravarthi; et al. (Archives of Microbiology, 2026)

Impact of lifestyle on salivary microbiota composition and antibiotic resistance in adult periodontitis patients - Saranya S; Saveetha Priya V; Roja B; Shreejaa C; SenthilKumar N; Chellapandi P (Antonie van Leeuwenhoek, 2026)

Experimental and theoretical insights into electronic structure modulated CoMoO4/Mo2TiC2TX-MXene coupling as a dual-functional electrode for supercapattery and oxygen evolution reaction - J. Adithya Shuhruth; P. Nitesh; N. Ambikeswari; C. Sengottaiyan; Masamichi Yoshimura; B. Neppolian; Senthilkumar Ramasamy; Manikandan Kandasamy; T. Kavinkumar (Chemical Engineering Journal, 2026)

Isolation of microcrystalline cellulose from vegetable waste biomass and its potential as a high-performance green reinforcement in biocomposites - Indran Suyambulingam; Raja Somasundaram; Divya Divakaran; Senthilkumar Boominathan; P. Senthamaraikannan; Nadir Ayrilmis; Murni Handayani (Bioresource Technology Reports, 2025)

Retraction notice to “Investigation of pure and g-C3N4 loaded CdWO4 photocatalytic activity on reducing toxic pollutants” [Chemosphere 291, Part 3, March 2022, 133090] - S.P. Keerthana; R. Yuvakkumar; P. SenthilKumar; G. Ravi; S.I. Hong; Dhayalan Velauthapillai (Chemosphere, 2025)

The Impact Assessment of Mechanized Transplanting of Sugarcane Settlings Using Economic Surplus Approach - K. P. Saha; Dushyant Singh; T. Senthilkumar; S. P. Singh; Rajni Jain; Manoj Kumar; V. Bhushanababu (Sugar Tech, 2025)

Efficacy of 6-nitrobenzo[d]thiazol-2 Amine Derivative (N3) in Mitigating PTZ-Induced Epileptic Conditions Via Modulation of Inflammatory and Neuroprotective Pathways in-vivo Zebrafish - Karthikeyan Ramamurthy; S. P. Ramya Ranjan Nayak; S. Madesh; Siva Prasad Panda; K. Manikandan; Rajakrishnan Rajagopal; Ahmed Alfarhan; Senthilkumar Palaniappan; Ajay Guru; M. K. Kathiravan; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

Recent progress in nanocellulose-based biocomposites for bone tissue engineering and wound healing applications - V. Parthasarathy; P. Senthil Kumar; Annie Aureen Albert; Senthilkumar Krishnasamy; M. Chandrasekar (Carbohydrate Polymers, 2025)

Short-Term Response of Mandous Severe Cyclone on Coastal Water Quality Along Southwestern Bay of Bengal, India - Subhasis Pradhan; P. Senthilkumar; Umakanta Pradhan; Subrat Naik; Rabindra Kumar Sahoo; Anitha Gera; Uma Sankar Panda; Pravakar Mishra; M. V. Ramana Murthy; P. Vipin Babu (Pure and Applied Geophysics, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Combined effects of salt-tolerant varieties and improved nutrient management practices on rice yield and profitability under salt-affected soils in the West African Sahel - Ali Ibrahim; Jean Eric P. Kaboré; Senthilkumar Kalimuthu; Baboucarr Manneh; Omar Ndaw Faye; Madiama Cissé; Kazuki Saito (Field Crops Research, 2025)

Genetic analysis of growth traits in Salem Black goats under farm conditions - Akshata Patil; D. Cauveri; P. Devendran; J. Muralidharan; P. Senthilkumar (Tropical Animal Health and Production, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Genetic diversity studies between Ipomoea wild species and cultivated sweet potato (Ipomoea batatas (L.) Lam.) using SSR markers - M.S. Amritha; O.G. Dhanya; Aswathy G.H. Nair; P. Vidya; Senthilkumar K. Muthusamy; C. Mohan (South African Journal of Botany, 2024)

Shrimp classification for white spot syndrome detection through enhanced gated recurrent unit-based wild geese migration optimization algorithm - L. Ramachandran; S. P. Mangaiyarkarasi; A. Subramanian; S. Senthilkumar (Virus Genes, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

BIN1 in the Pursuit of Ousting the Alzheimer’s Reign: Impact on Amyloid and Tau Neuropathology - Ishnoor Kaur; Tapan Behl; G. Sundararajan; P. Panneerselvam; A. R. Vijayakumar; G. P. Senthilkumar; T. Venkatachalam; Dharmender Jaglan; Shivam Yadav; Khalid Anwer; Neeraj Kumar Fuloria; Aayush Sehgal; et al. (Neurotoxicity Research, 2023)

Short-chain per- and polyfluoralkyl substances (PFAS) effects on oxidative stress biomarkers in human liver, kidney, muscle, and microglia cell lines - Megan E. Solan; Camryn P. Koperski; Sanjanaa Senthilkumar; Ramon Lavado (Environmental Research, 2023)

Growth kinetics of an Indian isolate of highly pathogenic porcine reproductive and respiratory syndrome virus in MARC-145 cells - Subbiah Kombiah; Dhanapal Senthilkumar; Manoj Kumar; Panickan Sivasankar; Vijendra P. Singh; Katherukamem Rajukumar (VirusDisease, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Identification of potential MTAs and candidate genes for juice quality- and yield-related traits in Saccharum clones: a genome-wide association and comparative genomic study - Shanmugavel Senthilkumar; K. K. Vinod; Selvaraj Parthiban; Prathima Thirugnanasambandam; Thalambedu Lakshmi Pathy; Nandita Banerjee; Thelakat Sasikumar Sarath Padmanabhan; P. Govindaraj (Molecular Genetics and Genomics, 2022)

Investigation of Geochemical Characterization and Groundwater Quality with Special Emphasis on Health Risk Assessment in Alluvial Aquifers, South Africa - P. P. Mthembu; V. Elumalai; M Senthilkumar; J. Wu (International Journal of Environmental Science and Technology, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Biostimulant activity of sulfated polysaccharide extract from red seaweed Halymenia dilatata on yield of Mung bean in greenhouse conditions - S. Vinoth; P. Gurusaravanan; M. Arun; M. Saradhadevi; N. Senthilkumar; P. Gowtham; S. R. Sivakumar (Journal of Applied Phycology, 2021)

Comparative bioefficacy of Bacillus and Pseudomonas chitinase against Helopeltis theivora in tea (Camellia sinensis (L.) O.Kuntze - M. Suganthi; S. Arvinth; P. Senthilkumar (Physiology and Molecular Biology of Plants, 2020)

Effects of PCB126 and PCB153 on telomerase activity and telomere length in undifferentiated and differentiated HL-60 cells - Xing Xin; P. K. Senthilkumar; Jerald L. Schnoor; Gabriele Ludewig (Environmental Science and Pollution Research, 2016)

Diagnosis of Mycobacterium bovis in Captive Sloth Bears (Melursus ursinus) by Polymerase Chain reaction - M. Veeraselvam; R. Sridhar; T. M. A. Senthilkumar; P. Perumal; M. G. Jayathangaraj (Proceedings of the Zoological Society, 2015)

Synthesis of novel 4-hydroxycoumarin derivatives: evaluation of antimicrobial, antioxidant activities and its molecular docking studies - M. Govindhan; K. Subramanian; K. Chennakesava Rao; K. Easwaramoorthi; P. Senthilkumar; P. T. Perumal (Medicinal Chemistry Research, 2015)

Surface Modification of Sediment with Surfactant for Capping Material on Contaminated Coastal Sediment - Young-Chae Song; B. Subha; J. H. Woo; H. J. Lim; P. Senthilkumar (Water, Air, & Soil Pollution, 2014)

Risk modulation of GSTM1–GSTT1 interactions to head and neck cancer in tobacco users - K. P. Senthilkumar; R. Thirumurugan (Molecular Biology Reports, 2014)

Computational analysis of deleterious missense mutations in aspartoacylase that cause Canavan’s disease - K. Sreevishnupriya; P. Chandrasekaran; A. Senthilkumar; R. Sethumadhavan; V. Shanthi; P. Daisy; J. Nisha; K. Ramanathan; R. Rajasekaran (Science China Life Sciences, 2012)

In vitro cytotoxicity and induction of apoptosis by ruthenium(II) complexes in HL-60 and K-562 - S. Bhattacharya; Subhas S. Karki; R. Suresh; L. Manikandan; G. P. Senthilkumar; M. Gupta; Upal K. Mazumder; R. Balaji; K. Murali (Medicinal Chemistry Research, 2012)

Evaluation of the cocktail recombinant antigens, LipL32 and LipL41 for serodiagnosis of canine leptospirosis - M. Subathra; T. M. A. Senthilkumar; P. Ramadass; V. Ramaswamy (World Journal of Microbiology and Biotechnology, 2011)

Recycle in upflow anaerobic sludge blanket reactor on treatment of real textile dye effluent - G. Gnanapragasam; M. Senthilkumar; V. Arutchelvan; P. Sivarajan; S. Nagarajan (World Journal of Microbiology and Biotechnology, 2010)

Serodiagnosis of bovine leptospirosis by IgG-Enzyme-Linked Immunosorbent Assay and Latex Agglutination Test - T. M. A. Senthilkumar; M. Subathra; P. Ramadass; V. Ramaswamy (Tropical Animal Health and Production, 2010)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Characterization of multiple promoters and transcript stability in the sacB–sacC gene cluster in Zymomonas mobilis - V. Senthilkumar; J. Rajendhran; S. J. W. Busby; P. Gunasekaran (Archives of Microbiology, 2009)

Effect of different level and source of copper supplementation on immune response and copper dependent enzyme activity in lambs - P. Senthilkumar; D. Nagalakshmi; Y. Ramana Reddy; K. Sudhakar (Tropical Animal Health and Production, 2009)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Induction of endophytic colonization in rice (Oryza sativa L.) tissue culture plants by Azorhizobium caulinodans - M. Senthilkumar; M. Madhaiyan; S. P. Sundaram; H. Sangeetha; S. Kannaiyan (Biotechnology Letters, 2008)

Purification and Partial Characterization of Antifungal Peptides from Soybean Endophyte-Paenibacillus sp strain HKA-15 - M. Senthilkumar; V. Govindasamy; P. Dureja; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2007)

Effects of Copper Sulfate and Copper Nitrate in Aquatic Medium on the Restoration Potential and Accumulation of Copper in Stem Cuttings of the Terrestrial Medicinal Plant, Portulaca Oleracea Linn - S. Mohanapriya; P. Senthilkumar; S. Sivakumar; M. Dineshkumar; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Plant Growth–Promoting Methylobacterium Induces Defense Responses in Groundnut (Arachis hypogaea L.) Compared with Rot Pathogens - M. Madhaiyan; B. V. Suresh Reddy; R. Anandham; M. Senthilkumar; S. Poonguzhali; S. P. Sundaram; Tongmin Sa (Current Microbiology, 2006)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Concentrations and Profiles of Polychlorinated Biphenyls, -Dibenzo-p-Dioxins and -Dibenzofurans in Livers of Mink from South Carolina and Louisiana, U.S.A. - Carrie L. Tansy; Kurunthachalam Senthilkumar; Stephanie D. Pastva; Kurunthachalam Kannan; William W. Bowerman; Shigeki Masunaga; John P. Giesy (Environmental Monitoring and Assessment, 2003)

Molecular phylogeny of mangroves VIII: Analysis of mitochondrial DNA variation for species identification and relationships in Indian mangrove Rhizophoraceae - M. Lakshmi; M. Parani; P. Senthilkumar; Ajay Parida (Wetlands Ecology and Management, 2002)

Mulberry-Silkworm Food Chain – A Templet to Assess Heavy Metal Mobility in Terrestrial Ecosystems - SPM. Prince; P. Senthilkumar; V. Subburam (Environmental Monitoring and Assessment, 2001)

Molecular phylogeny of mangroves VII. PCR-RFLP of trnS-psbC and rbcL gene regions in 24 mangrove and mangrove-associate species - M. Parani; M. Lakshmi; B. Ziegenhagen; M. Fladung; P. Senthilkumar; A. Parida (Theoretical and Applied Genetics, 2000)

Butyltin compounds in sediment and fish from the Polish Coast of the Baltic Sea - Kurunthachalam Senthilkumar; Carolyn A. Duda; Daniel L. Villeneuve; Kurunthachalam Kannan; Jerzy Falandysz; John P. Giesy (Environmental Science and Pollution Research, 1999)

Analysis of rice mitochondrial genome organization using pulsed-field gel electrophoresis - P. Senthilkumar; K. K. Narayanan (Journal of Biosciences, 1999)

Butyltin Compounds in River Otters (Lutra canadensis) from the Northwestern United States - K. Kannan; R. A. Grove; K. Senthilkumar; C. J. Henny; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1999)

Molecular phylogeny of mangroves V. Analysis of genome relationships in mangrove species using RAPD and RFLP markers - M. Parani; M. Lakshmi; P. Senthilkumar; Nivedita Ram; A. Parida (Theoretical and Applied Genetics, 1998)

Occurrence of Butyltin Compounds in Tissues of Water Birds and Seaducks from the United States and Canada - K. Kannan; K. Senthilkumar; J. E. Elliott; L. A. Feyk; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1998)